Revision of the new Australian genus Artoriopsis in a new subfamily of wolf spiders, Artoriinae (Araneae: Lycosidae) - Framenau, Volker W. (Zootaxa, 2007)
new Australian wolf spider genus Artoriopsis is established with Artoriopsis expolita (L. Koch, 1877), comb. nov.  as type species. Six further species, A. anacardium sp. nov., A. eccentrica sp. nov., A. joergi sp. nov., A. klausi sp. nov.,  A. melissae sp. nov. and A. whitehouseae sp. nov. complete the Australian fauna. Artoriopsis gen. nov. shows affinities  with the Australasian genera Artoria Thorell, 1877 and Anoteropsis Koch, 1877, but differs by a distinct colour pattern of  the opisthosoma (a dark diamond-shaped spot is cut in half by the light lanceolate cardiac mark). The basoembolic apophysis  of the male pedipalp is narrowest at its base and comparatively weakly sclerotised, whereas it is widest at its base  and strongly sclerotised in Artoria and inverted L-shaped in Anoteropsis. The median septum of the female epigyne  forms a distinct plate that covers the atrium, although it is reduced in A. eccentrica sp. nov. and A. joergi sp. nov. Representatives  of the genus Artoriopsis gen. nov. have so far only been found in Australia, where they are most diverse in the  southern half of the country, although one species, A. anacardium sp. nov., is known from the tropical north.  A new wolf spider subfamily, Artoriinae (type genus Artoria Thorell, 1877), is established to accommodate the following  genera: Anoteropsis L. Koch, 1878, Artoria Thorell, 1877 (= Lycosula Roewer, 1960, syn. nov.), Artoriopsis gen.  nov., Diahogna Roewer, 1960, Lycosella Thorell 1890, Notocosa Vink, 2002, Syroloma Simon, 1900, Tetralycosa  Roewer, 1960, and two unnamed genera. The new synonymy of Lycosula with Artoria places the following species into Artoria: A. thorelli (Berland, 1929) comb. nov., A. hebridisiana (Berland, 1938), comb. nov. and A. minima (Berland,  1938) comb. nov. Artoriinae subfam. nov. are characterised by the presence of a basoembolic apophysis on the male  pedipalp, unique within the Lycosidae. Artoriinae subfam. nov. are restricted to the Oriental, Australasian and Pacific  regions with the centre of diversity in Australia and New Zealand.